Implementasi penyimpanan obat high alert kategori lasa (look alike sound alike) - Zaijul, Ummu; Nadjamuddin, Mirfaidah; Jannah, Miftahul (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Look-Alike, Sound-Alike (LASA) High Alert medications carry a high risk of medication errors due to similarities in name, shape, or packaging. Errors in storage and labeling of LASA medications can seriously impact patient safety, requiring a standardized storage system that aligns with hospital pharmaceutical service standards. Purpose: To describe the implementation of LASA High Alert medication storage based on applicable standard operating procedures. Method: This study used a qualitative descriptive design with observation and semi-structured interviews. Data were collected in May–June 2025 through checklist observations, interviews with pharmacists and pharmacist assistants, and documentation. Data analysis was conducted descriptively using a Guttman scale of compliance assessment. Results: Observations indicated that storage of LASA High Alert medications was implemented with a 100% compliance rate, categorized as very good. LASA medications were stored separately, labeled specifically, arranged alphabetically, applying the FEFO and FIFO principles, and using the Tall Man Lettering method. Conclusion: Implementation of LASA High Alert medication storage was very successful and met standards, supporting efforts to improve patient safety. Keywords: High Alert; Lasa; Medication Storage; Patient Safety. Pendahuluan: Obat High Alert kategori Look Alike Sound Alike (LASA) memiliki risiko tinggi menyebabkan medication error akibat kemiripan nama, bentuk, atau kemasan. Kesalahan dalam penyimpanan dan pelabelan obat LASA dapat berdampak serius terhadap keselamatan pasien, sehingga diperlukan sistem penyimpanan yang terstandarisasi dan sesuai dengan standar pelayanan kefarmasian rumah sakit. Tujuan: Untuk mendeskripsikan implementasi penyimpanan obat High Alert kategori LASA berdasarkan standar operasional prosedur yang berlaku. Metode: Penelitian ini menggunakan desain deskriptif kualitatif dengan pendekatan observasi dan wawancara semistruktur. Data dikumpulkan pada Mei–Juni 2025 melalui observasi checklist, wawancara terhadap apoteker dan asisten apoteker, serta dokumentasi. Analisis data dilakukan secara deskriptif menggunakan sistem penilaian persentase kesesuaian berdasarkan skala Guttman. Hasil: Hasil observasi menunjukkan bahwa penyimpanan obat High Alert kategori LASA telah dilaksanakan dengan tingkat kesesuaian 100% dan masuk dalam kategori sangat baik. Obat LASA disimpan terpisah, diberi label khusus, disusun secara alfabetis, menerapkan prinsip FEFO dan FIFO, serta menggunakan metode Tall Man Lettering. Simpulan: Implementasi penyimpanan obat High Alert kategori LASA telah berjalan sangat baik dan sesuai standar, serta mendukung upaya peningkatan keselamatan pasien. Kata Kunci: High Alert; Keselamatan Pasien; Lasa; Penyimpanan Obat.